183k views
4 votes

(5x^(6)5x^(-2)125x2x^(4)2x^(-5) )/(2x^(5)5x^(-3)2x^(6\\) )

User Taliek
by
4.9k points

1 Answer

4 votes


\cfrac{5x^6 5x^(-2)125x 2x^4 2x^(-5)}{2x^5 5x^(-3) 2x^6}\implies \cfrac{5\cdot 5\cdot 125\cdot 2\cdot 2}{2\cdot 5\cdot 2}\cdot \cfrac{x^6 x^(-2)x x^4 x^(-5)}{x^5 x^(-3) x^6} \\\\\\ \cfrac{ 5\cdot 125}{1}\cdot \cfrac{x^(6-2+1+4-5)}{x^(5-3+6)}\implies 125\cdot \cfrac{x^4}{x^8}\implies 125\cdot \cfrac{1}{x^8 x^(-4)}\implies \cfrac{125}{x^(8-4)}\implies {\Large \begin{array}{llll} \cfrac{125}{x^4} \end{array}}

User Nathan Kamenar
by
5.8k points